(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Non-communicable diseases (NCDs) have become burning issues worldwide, especially among the elderly individuals. Bangladeshi elderly is also susceptible cohort to NCDs for its recent epidemiologic transition and the NCDs is casting as prominent risk for major mortality and morbidity related issues. Objectives: To find out the prevalence of common NCDs and its risk factors among the Bangladeshi retired military personnel. Methods: This cross-sectional study was conducted among the retired military personnel admitted in Combined Military Hospital (CMH), Savar from January 2019 to July 2019. A face-to-face interview was carried out among the respondents using a semi-structured questionnaire. Results: Among 153 retired military personnel; most common NCDs were hypertension (80.4%), diabetes mellitus 66.7%, ischemic heart disease37.3% and only 3.9 % had low back pain. Most of them accessed their health in CMH (66.7%), where 17.6% reported to Govt. hospital and only a minor portion (15.7%) to private hospital. Moreover, 70.6% of them were not willing to regular health check-up. Conclusions: The most common NCDs were hypertension, diabetes mellitus and ischemic heart disease. This study concluded with a few intervention strategies and community-based health promotion programs to reduce the burden of NCDs among the retired military personnel. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 35-39